ALTERATIONS IN THE BIOCHEMICAL PROFILES AND METABOLIC ENZYMES IN TISSUES OF LABEO ROHITA - G. SREEKALA,; BELA ZUTSHI, (The Bioscan, 2012)
The present study is aimed on the estimation of the biochemical composition and assay of metabolic enzymes in liver, kidney and brain tissues of L. rohita reared in the freshwater lakes of Bangalore. The study was conducted for a period of 15 months in three sites- Hebbal fish farm (control site), Vengaiah lake (Lake A) which is being used for recreation purpose and Yellamallappa chetty lake (Lake B) which receives sewage and industrial pollutants and variations in these organic constituents was recorded. The study revealed a considerable reduction in the levels of proteins and glycogen whereas the levels of cholesterol showed a significant increase in the tissues of test fish sampled from lake (B) whereas fish tissues obtained from the lake (A) did not show significant variation when compared to those of control. Metabolic enzymes such as succinic-, malic- and lactic dehydrogenases also showed a considerable variation in the tissues of test fish sampled from lake (B) when compared to that of control to meet the energy demands in hypoxic condition in polluted lake water.